SAXS Structural Studies of Dps from Deinococcus radiodurans Highlights the Conformation of the Mobile N-Terminal Extensions. Issue 5 (10th March 2017) - Santos, Sandra P.; Cuypers, Maxime G.; Round, Adam; Finet, Stephanie; Narayanan, Theyencheri; Mitchell, Edward P.; Romão, Célia V.
Abstract: The radiation-resistant bacterium Deinococcus radiodurans contains two DNA-binding proteins from starved cells (Dps): Dps1 (DR2263) and Dps2 (DRB0092). These are suggested to play a role in DNA interaction and manganese and iron storage. The proteins assemble as a conserved dodecameric structure with structurally uncharacterised N-terminal extensions. In the case of Dr Dps1, these extensions have been proposed to be involved in DNA interactions, while in Dr Dps2, their function has yet to be established. The reported data reveal the relative position of the N-terminal extensions to the dodecameric sphere in solution for both Dps. The low-resolution small angle X-ray scattering (SAXS) results show that the N-terminal extensions protrude from the spherical shell of both proteins. The SAXS envelope of a truncated form of Dr Dps1 without the N-terminal extensions appears as a dodecameric sphere, contrasting strongly with the protrusions observed in the full-length models. The effect of iron incorporation into Dr Dps2 was investigated by static and stopped-flow SAXS measurements, revealing dynamic structural changes upon iron binding and core formation, as reflected by a quick alteration of its radius of gyration. The truncated and full-length versions of Dr Dps were also compared on the basis of their interaction with DNA to analyse functional roles of the N-terminal extensions. Dr Dps1 N-terminal protrusions appear to be directly involved with DNA, whilst those from Dr Dps2 are indirectly associated with DNA binding. Furthermore, detection of Dr Dps2 in the D. radiodurans membrane fraction suggests that the N-terminus of the protein interacts with the membrane. Graphical Abstract: Highlights: Location of the Dr Dps N-terminal extensions protruding from the dodecamer spheres. Iron nano-cluster formation in Dps2 leads to dynamic conformational change. Function of the Dps2 N-terminal extension and its association with the membrane